(untitled) (NTU Journal of Agriculture and Veterinary Science, 2021)
The studies were conducted in the apiary laboratory, apiary store and the external shed of the Plant Protection Department/Department of Plant Protection/College of Agriculture and Forestry/Mosul University during the year 2019-2020. Before using plant powders (black arum, oleander, and cinnamon) to control the wax moth, the effect of the powders on honeybee colonies was tested. The results did not show any negative effect of the powders under study on bees, and bees mortality as a result of treating frames with powders were not recorded. As for the effect of plant powders on the wax-moth, the results showed the lethal effect of plant powders (black arum, oleander and cinnamon) on the Wax moth larvae stage in the laboratory. All plant powders led to satisfactory mortality rates after a week of treatment, especially the black arum powder treatment which differed from the other treatments, and recorded the highest mortality rate of 83.3%, followed by oleander powder with a mortality rate of 63.3%, then cinnamon powder treatment which resulted in the lowest mortality rate of 50.0% during the same period. It was noted that mortality rates differed among treatments for different dates. Interaction treatment of black arum powder and outdoor storage method with leaving a space between frames after a week of treatment recorded the highest mortality rate which was. The rates of larval mortality varied according to the method of storage, arranging the frames and the dates of data recording. Natural mortality rates of insect larvae were recorded in the control treatment, especially in outdoor storing frames, when leaving a space between frames. The control treatment did not record any natural mortality for larvae when using the storage method inside the store, regardless of the distance between frames or the dates of data recording.